Subsystem of rheological forming modelling in integrated CAD/CAPP/CAM system in machine building - Stupnytskyy, V. (Видавництво Львівської політехніки, 2012)
In the article the brought analysis of automated technological planning process for the machine-building production (ІСАМ) trends. The offered perfection of ІСАМ structure of the system as introduction of the Computer Aided Forming sub-system (CAF-system). The brought arguments over in relation to introduction of conception of the parallel engineering, introduction of CALS – technologies and functionally-oriented technologies. Описано аналіз процесу автоматизованого технологічного планування машинобудівного виробництва (ІСАМ). Запропоновано вдосконалення структури системи ІСАМ із впровадженням підсистеми автоматизованого формування (CAF-системи).Наведено аргументи щодо впровадження концепції паралельної розробки, впровадження CALS-технологій та функціонально-орієнтованих технологій.
Keywords: automated technological planning process; CALS; CAF; rheological modelling; процес автоматизованого технологічного планування; CALS; CAF; реологічне моделювання